A new species of the genus Liuixalus (Anura: Rhacophoridae) from southern China - Yang, Jian-Huan; Rao, Ding-Qi; Wang, Ying-Yong (Zootaxa, 2015)
A new tree frog species of the genus Liuixalus was described from Heishiding Nature Reserve, Guangdong Province, China based on a combination of morphological characters and molecular phylogenetic analyses. Liuixalus feii sp. nov. is distinguished from its congeners by a combination of following characters: small size (SVL 16.2–17.6 mm in adult males and 18.0–18.7 mm in adult females); snout obtusely pointed; tympanum distinct, about half size of eye diameter; nostril closer to eye than to the tip of snout; fingers free of webbing; toe III longer than toe V; toes weakly webbed; tibiotarsal articulation reaching the naris or loreal; dorsal skin smooth and scattered with fine granulars; a subtle longitudinal median ridge present on dorsum; weak skin folds present on dorsal surface of body and thighs; supratympanic fold distinct and curved; ventral surface dull white with more or less irregular dark spots; iris bicolored. The new species appears to be forest-dependent and to date has only been found on the forest floor in primary forests at elevations between 350–800 m. Based on our molecular analyses, we consider Liuixalus catbaensis as a junior synonym of L. calcarius. Thus, with the description of the new species, the genus Liuixalus hitherto contains five recognized species, four of which are endemic to China.